Geldanamycin Reduces Acute Respiratory Distress Syndrome and Promotes the Survival of Mice Infected with the Highly Virulent H5N1 Influenza Virus - Wang, Chengmin; Liu, Pengpeng; Luo, Jing; Ding, Hua; Gao, Yan; Sun, Lei; Luo, Fubing; Liu, Xiaodong; He, Hongxuan (Frontiers in Cellular and Infection Microbiology, 2017)
Infection of lethal influenza viruses lead to the acute lung injury (ALI) or acute respiratory distress syndrome (ARDS),which may relate to the activation of the host’s immune system. Here, in our study, Male C57BL/6 mice were infected with 10 LD50 of influenza virus H5N1, and treated with geldanamycin or oseltamivir after 2 h infection. Lung injury was assessed by histopathology on days 4 and 7. The viral load was quantified by NP gene expression level on days 2, 4 and 7. Cytokines and chemokines in bronchoalveolar lavage fluids and inflammatory cells were analyzed at different time points. The results showed that Geldanamycin administration prolonged survival in mice, and exhibited a dramatic reduction in lung injury and pulmonary inflammatory compared with other mice. Viral loads in geldanamycin-treated mice also significantly reduced compared with non-treated ones, but not as much as oseltamivir treated ones. Furthermore, geldanamycin treatment markedly reduced the production of major proinflammatory cytokines and chemokines, and attenuated the infiltration and activation of immune cells, but it did not alter the generation of virus-neutralizing antibodies. In a conclusion, geldanamycin play an important role on attenuating virus infection–induced ALI/ARDS by reducing the host inflammatory responses and may provide important reference for clinical medication..